Canadian Municipalities and Conditions of Fiscal Austerity in International Perspective: A Report and Some Observations - Lightbody, James; Walker, David (Urban History Review / Revue d'histoire urbaine, 1987)
In this report, the authors summarize the well-known historic conditions underpinning the current fiscal plight of Canadian municipalities. Within this overall context the austerity strategies employed by local government officials elsewhere in the world become increasingly suggestive for authorities desperately trying to reconcile service demands with fiscal prudence. Some general observations from recent reports to the generation-old Fiscal Austerity and Urban Innovation project, coupled with preliminary results of the authors' own field research, are advanced.